The Role of Catalysts on Composites Properties: A Case Study on Motorcycle Body Cover - Kautzar Rizki Diptaseptian; Wijianto Wijianto; Pramuko Ilmu Purboputro (Automotive Experiences, 2019)
Today, modification on motorcycle body cover has become a new automotive business. The main components for modifying the motor body cover are glass fibre, resin and catalyst. Catalysts are substances that can accelerate reactions, the more catalyst composition, the less time it takes to react. Therefore, this study aims to determine the effect of variations in catalysts on composite properties. The test is carried out by giving the catalyst in 4 variations (2.5%, 5%, 10%, and 20%) to 157 BQTN resin. The specimen was tested using ASTM D-256 for impact/hardness, ASTM D-790 for bending, and ASTM D-638 for tensile strength. During this study, we found that the 2.5% catalyst give good results for impact, bending, tensile strength, and also modulus young.